2010
DOI: 10.1007/s00431-010-1316-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, adipokines and ghrelin in overweight and obese schoolchildren: results of a 1-year lifestyle intervention programme

Abstract: The aim of this study was to evaluate the effect of a lifestyle intervention programme (nutrition and exercise counselling) on metabolic syndrome (MS) components, adipokines (leptin, adiponectin) and ghrelin levels in overweight children. A total of 61 overweight children aged 7-9 years (≥ 85th body mass index (BMI) percentile; 27 boys/34 girls) were randomly assigned and completed a 1-year individual (IT) or group-based treatment (GT). Anthropometric and biochemical parameters were assessed at baseline, at 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 46 publications
6
35
0
Order By: Relevance
“…However, no correlation was found between adiponectin and TG or low-density lipoprotein cholesterol (LDLc) [38]. Oppositely, no relation between lipid profile and adiponectin was reported in other paediatric studies [14,21]. Concerning adiponectin multimers, while LMW adiponectin seems to be linked with a worse lipid profile, through a positive association with TG [5], HMW adiponectin has shown opposite effects [6], even in PP individuals [11].…”
Section: Lipid Profilementioning
confidence: 93%
See 2 more Smart Citations
“…However, no correlation was found between adiponectin and TG or low-density lipoprotein cholesterol (LDLc) [38]. Oppositely, no relation between lipid profile and adiponectin was reported in other paediatric studies [14,21]. Concerning adiponectin multimers, while LMW adiponectin seems to be linked with a worse lipid profile, through a positive association with TG [5], HMW adiponectin has shown opposite effects [6], even in PP individuals [11].…”
Section: Lipid Profilementioning
confidence: 93%
“…Some data reported a negative association between adiponectin and both SBP and diastolic BP (DBP) [13,16,36], or with SBP alone [25,29,34,37,70]. Fewer studies describe the absence of association between adiponectin and BP [14,27,49].…”
Section: Blood Vessels and Blood Pressure (Bp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, another study found no impact on TA levels after a nutritional counseling program in prepubertal Portuguese children, despite the improvement in BMI z-score (BMIzsc) and blood lipids (21). Different results were found in a study involving obese adolescent boys, as improvements in adiponectin levels were obtained both by energy restriction and by exercise separately, moreover, cumulative effects were present when both approaches were combined (22).…”
mentioning
confidence: 93%
“…The increases in BMI during childhood may be related to the development and acceleration of adverse cardiometabolic risk factors, such as hypertension, dyslipidemia (high TG and low highdensity lipoprotein (HDL) cholesterol), hyperinsulinemia and glucose intolerance, known as MES [1]. The increasing obesity prevalence in childhood and adolescence has increased the prevalence of MES.…”
Section: Introductionmentioning
confidence: 99%